Red Coats and Wild Birds : How Military Ornithologists and Migrant Birds Shaped Empire - Greer, Kirsten A. (Book collections on Project MUSE., 2020)
"During the nineteenth century, Britain maintained a complex network of garrisons to manage its global empire. While these bases helped the British project power and secure trade routes, they served more than just a strategic purpose. During their tours abroad, many British officers engaged in formal and informal scientific research. In this ambitious history of ornithology and empire, Kirsten A. Greer tracks British officers as they moved around the world, just as migratory birds traversed borders from season to season"--